2007
DOI: 10.1093/jn/137.5.1314
|View full text |Cite
|
Sign up to set email alerts
|

Occupation Is More Important than Rural or Urban Residence in Explaining the Prevalence of Metabolic and Cardiovascular Disease Risk in Guatemalan Adults1

Abstract: Diet and activity pattern changes consequent to urbanization are contributing to the global epidemic of cardiovascular disease; less research has focused on activity within rural populations. We studied 527 women and 360 men (25-42 y), all rural-born and currently residing in rural or urban areas of Guatemala. We further classified rural male occupations as agricultural or nonagricultural. Overweight status (BMI > or = 25 kg/m(2)) differed by residence/occupation among men (agricultural-rural, 27%; nonagricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 35 publications
4
45
0
1
Order By: Relevance
“…Men still perform the field activities that require high energy expenditure, while women are devoted to housework. 5 Another investigation developed using the same population as in this study showed that men were more active than women in relation to leisure, commuting and work, while women were more active than men in the household domain. 21 We observed in this study that there were occurrences of three or more metabolic syndrome components at rates greater than would be predicted by chance.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Men still perform the field activities that require high energy expenditure, while women are devoted to housework. 5 Another investigation developed using the same population as in this study showed that men were more active than women in relation to leisure, commuting and work, while women were more active than men in the household domain. 21 We observed in this study that there were occurrences of three or more metabolic syndrome components at rates greater than would be predicted by chance.…”
Section: Discussionmentioning
confidence: 68%
“…Similar findings have also been shown in studies developed in rural areas in Brazil 4 and other countries. 5,20 There seems to be a pattern of metabolic syndrome occurrence in rural areas that is characterized by higher prevalence among women. This phenomenon might be determined by people's occupations in this region, which differ greatly according to sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La prevalencia del síndrome metabólico fluctúa ampliamente dependiendo de la población estudiada, teniendo esto en cuenta, en el estudio de Gregory C, et al, encuentran en la población americana una prevalencia de 24% en adultos guatemaltecos que varía desde 7 al 28%, de acuerdo a que se tratasen de agricultores, de la población rural y urbana (11) .…”
Section: Introductionunclassified